Blended Learning: Issues Related to Successful Implementation (International Journal of Scientific Research and Management (IJSRM), 2021)
This study explores the underlying theoretical principles that provide the basis for the design and implementation of blended learning classes. It discusses how online meetings and face-to-face sessions can be integrated in today’s classrooms. Many studies and experiences have been reviewed in accordance with the preparation, implementation and evaluation of blended Learning classes. A summary of collected knowledge shows that blended learning has been favorable in today’s educational environment. Most studies show that once infrastructure and technological tools are provided, many problems such as crowded classrooms and students’ motivation toward learning will be settled via the utilization of Blended Learning. Moreover, the positive and comfortable Blended Learning environments will change the attitudes of students and teachers toward learning and teaching as time and place of lessons will not be a difficulty for both. However, achieving the benefits of Blended Learning models will not yield their fruits unless reviewing matters of training, planning and legislation are done.